Development and Validation of a Real-Time PCR for Detection of Pathogenic Leptospira Species in Clinical Materials - Ahmed, Ahmed; Engelberts, Mirjam F. M.; Boer, Kimberly R.; Ahmed, Niyaz; Hartskeerl, Rudy A. (PLOS ONE, 2009)
Available serological diagnostics do not allow the confirmation of clinically suspected leptospirosis at the early acute phase of illness. Several conventional and real-time PCRs for the early diagnosis of leptospirosis have been described but these have been incompletely evaluated. We developed a SYBR Green-based real-time PCR targeting secY and validated it according to international guidelines. To determine the analytical specificity, DNA from 56 Leptospira strains belonging to pathogenic, non-pathogenic and intermediate Leptospira spp. as well as 46 other micro-organisms was included in this study. All the pathogenic Leptospira gave a positive reaction. We found no cross-reaction with saprophytic Leptospira and other micro-organisms, implying a high analytical specificity. The analytical sensitivity of the PCR was one copy per reaction from cultured homologous strain M 20 and 1.2 and 1.5 copy for heterologous strains 1342 K and Sarmin, respectively. In spiked serum & blood and kidney tissue the sensitivity was 10 and 20 copies for M 20, 15 and 30 copies for 1342 K and 30 and 50 copies for Sarmin. To determine the diagnostic sensitivity (DSe) and specificity (DSp), clinical blood samples from 26 laboratory-confirmed and 107 negative patients suspected of leptospirosis were enrolled as a prospective consecutive cohort. Based on culture as the gold standard, we found a DSe and DSp of 100% and 93%, respectively. All eight PCR positive samples that had a negative culture seroconverted later on, implying a higher actual DSp. When using culture and serology as the gold standard, the DSe was lower (89%) while the DSp was higher (100%). DSe was 100% in samples collected within the first – for treatment important - 4 days after onset of the illness. Reproducibility and repeatability of the assay, determined by blind testing kidney samples from 20 confirmed positive and 20 negative rodents both appeared 100%. In conclusion we have described for the first time the development of a robust SYBR Green real-time PCR for the detection of pathogenic Leptospira combined with a detailed assessment of its clinical accuracy, thus providing a method for the early diagnosis of leptospirosis with a well-defined satisfactory performance.